2021
DOI: 10.3389/fvets.2021.704598
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Characterisation of GLUT1, MMP3 and NRF2 in Osteosarcoma

Abstract: Osteosarcoma (OSA) is an aggressive bone malignancy. Unlike many other malignancies, OSA outcomes have not improved in recent decades. One challenge to the development of better diagnostic and therapeutic methods for OSA has been the lack of well characterized experimental model systems. Spontaneous OSA in dogs provides a good model for the disease seen in people and also remains an important veterinary clinical challenge. We recently used RNA sequencing and qRT-PCR to provide a detailed molecular characteriza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“… 16 , 19 , 40 , 41 Overexpression of Glut1 has been commonly observed in many cancers, such as osteosarcoma, lung cancer, and lymphoma. 41 , 42 In addition, Glut1 is considered to be the main isoform expressed in human osteosarcoma cell lines (SaOS2, MG‐63, and U2‐OS cell lines). 43 Previous studies have also shown that targeting glucose metabolism has the potential to provide an effective approach for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 , 19 , 40 , 41 Overexpression of Glut1 has been commonly observed in many cancers, such as osteosarcoma, lung cancer, and lymphoma. 41 , 42 In addition, Glut1 is considered to be the main isoform expressed in human osteosarcoma cell lines (SaOS2, MG‐63, and U2‐OS cell lines). 43 Previous studies have also shown that targeting glucose metabolism has the potential to provide an effective approach for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose is a major source of energy in mammalian cells because it upregulates the expression of glycolytic enzymes such as Glut1, HK2, Pfkfb3/4, and LDHA to stimulate tumorigenesis 16,19,40,41 . Overexpression of Glut1 has been commonly observed in many cancers, such as osteosarcoma, lung cancer, and lymphoma 41,42 . In addition, Glut1 is considered to be the main isoform expressed in human osteosarcoma cell lines (SaOS2, MG‐63, and U2‐OS cell lines) 43 .…”
Section: Discussionmentioning
confidence: 99%
“…None of these loci are consistently associated across breeds, suggesting there may be a difference between breeds regarding genetic predisposition to developing OSA (89,90). In addition to the 34 genetic loci identified, genes have been identified as differentially expressed in canine OSA compared to non-tumor tissue, many of which have implications for growth and metastasis, and are potential drug targets (55, [91][92][93][94][95][96]. These genes have been identified utilizing canine OSA tumor tissue, and/or canine OSA cell lines.…”
Section: Similarities and DI Erences Between Osa Molecular Mechanisms...mentioning
confidence: 99%
“…Interestingly, increased expression of SLC2A1 (GLUT1) within tumors also resulted in poorer prognosis and a shorter disease free interval in people (101). SLC2A1/GLUT1 (see Figure 1) levels were also significantly increased in naturally occurring canine OSA tissue compared to normal bone tissue (55, 95). Inhibition of SLC2A1 and cellular glucose transport has been achieved by a number of pharmaceuticals, however, as with the MMP3 inhibitors, these have yet to be utilized in OSA trials in either people or dogs (102)(103)(104)(105).…”
Section: Shared Genes and Proteins Of Interest For Development Of Fut...mentioning
confidence: 99%
See 1 more Smart Citation